2015
DOI: 10.1039/c5cc01567g
|View full text |Cite
|
Sign up to set email alerts
|

Implantable nonenzymatic glucose/O2micro film fuel cells assembled with hierarchical AuZn electrodes

Abstract: Hierarchical AuZn dendrites revealed electrocatalytic properties towards the glucose oxidation and the four-electron O2 reduction. The micro fuel cell using AuZn electrodes generated a power density of 2.07 and 0.29 mW cm(-2) for glucose and human whole blood. The micro film fuel cell implanted into the rat brain produced ∼0.52 V continuously operating for more than 18 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Finally, it is worth be noticed that implantable nonenzymatic glucose/O 2 micro film fuel cells assembled with hierarchical AuZn electrodes were fabricated by Noh et al [73]. The micro fuel cell using AuZn electrodes generated a power density of 2.07 and 0.28 mW cm -2 for glucose and human whole blood, respectively.…”
Section: Au+oh -→ Au-oh Ads (1-λ) + λ E -mentioning
confidence: 99%
“…Finally, it is worth be noticed that implantable nonenzymatic glucose/O 2 micro film fuel cells assembled with hierarchical AuZn electrodes were fabricated by Noh et al [73]. The micro fuel cell using AuZn electrodes generated a power density of 2.07 and 0.28 mW cm -2 for glucose and human whole blood, respectively.…”
Section: Au+oh -→ Au-oh Ads (1-λ) + λ E -mentioning
confidence: 99%
“…AuNi alloys have also been studied by researchers in the field of catalysis. [31][32][33][34][35] Hosseini et al designed the nanostructured Cu/Ni/AuNi catalyst using the electrodeposition process followed by galvanic replacement technique. The electrocatalytic activity of Cu/Ni/AuNi electrodes for borohydride electrooxidation was much higher than that of flat Au catalyst.…”
Section: 6 9-12mentioning
confidence: 99%
“…31 Naveen et al fabricated AuNi@pTBA composite catalysts using the electrochemical deposition method and reported their better ORR catalytic activities and stabilities relative to the Pt/C catalyst. 35 Although great progress has been achieved in AuNi alloys field, the current applications of AuNi alloys are focused on catalytic oxidation of borohydride, 32 hydroquinone 33 or glucose, 34 the reports for electrocatalytic oxygen reduction reaction are rare, resulting in the lack of systematically studies on the catalytic mechanism of AuNi catalysts for ORR. Moreover, the composite or polymer in the catalysts may block the electron transfer and mass transport, which seriously hamper their catalytic activities, and the simple and pure metallic catalysts without the influence of composite or polymer usually give more physicochemical insights into the catalyst design.…”
Section: 6 9-12mentioning
confidence: 99%
“…Recently,Z hang and co-workers observed as tabilization effect of Au clusters on Pt for the oxygen reductionr eaction (ORR), and the resultant Au/Pt/C catalysts howed negligible ac-tivity degradation after 30 000 potential cycles under oxidizing conditions, [6] which suggested that Au might have great potentiala sa ne lectrocatalyst with excellent durability.U nfortunately,m onometallic Au atoms are much less active than Pt atoms for theO RR and fuel oxidationr eactions owing to weak adsorption of the reactant molecules. [7] Strategies used to enhance the catalytic performance of monometallic Au usually include alloying with 3d transition metalst of orm Au-M (M = Ni, [8] Zn, [9] Cu [10] )b imetallic nanostructures and/orr educing the size to increase the specific surface area. [11] These approaches have been demonstrated not only to lower the total cost of Au-based catalysts effectively but also to improvet he catalytic activities dramatically.A mong these inexpensive Au-M catalysts, Au-Cu alloys have shown promising potential in CO 2 reduction, [12] the hydrogen evolution reaction, [12a, 13] and the CO and glucose oxidationr eactions.…”
Section: Introductionmentioning
confidence: 99%